MARKETING POLITIK AKA CHOLIK DARLIN PADA AKUN YOUTUBE AKA CHOLIK TV MENUJU PEMILU 2024 - Yunita, Tiara; Ropik, Ainur; Anisyah, Siti (Jurnal Studi Ilmu Politik, 2024)
This research is entitled Aka Cholik Darlin’s Political Marketing on Aka Cholik TV’s Youtube Account towards the 2024 election which is motivated by political marketing carried out by Aka Cholik Darlin, he often uses social media with the YouTube platform which is often active, this marketing takes advantage of the advantages of social media in terms of ease of access for prospective voters. The aim of the research is to find out the marketing of legislative candidates in the 2024 election, Aka Cholik Darlin from the National Awakening Party via YouTube. This research uses Nifenegger’s political marketing theory according to Koteen. Data comes from primary data in this research obtained from interviews, and YouTube social media on the Aka Cholik Tv account, and secondary data from supporting literature and journals regarding the research topic. The data collection technique used is searching for data and information through documents. Data analysis techniques for data reduction, data analysis, and drawing conclusions. The research results show that Aka Cholik Darlin carries out his political marketing by using YouTube as political media, discussing a lot about political campaigns, outreach to the community and the younger generation. Based on the results of the political marketing analysis on the Aka Cholik TV Youtube account, in carrying out its political marketing via Youtube Aka Cholik takes advantage of the surrounding conditions or situations.